A between‐experiment analysis of relationships linking dietary protein intake and post‐weaning diarrhea in weanling pigs under conditions of experimental infection with an enterotoxigenic strain of Escherichia coli1. (18th September 2014) - Heo, Jung Min; Kim, Jae Cheol; Yoo, Jaehong; Pluske, John R.
Abstract Numerous experiments have demonstrated that feeding a lower protein diet decreases protein fermentation in the gastrointestinal tract (GIT) and reduces the incidence of post‐weaning diarrhea (PWD). However, there is a lack of holistic evidence underpinning the relationship between feeding a lower protein diet and PWD in relation to physiological responses and protein fermentation in the GIT. The scope of this article, therefore, will: (i) focus on the impact of dietary protein levels on selected indices of GIT health in weaned pigs without and with experimental infection with an enterotoxigenic strain of Escherichia coli; and (ii) attempt to conduct regression analysis to examine the relationships between dietary‐origin protein intake, nitrogen fermentation indices, fecal consistency and the incidence of PWD. We used datasets generated from a series of four intensive experiments in weaned pigs. The collective results derived from these datasets indicate that restriction of daily protein intake to less than 60 g through feeding a lower protein diet for as little as 7 days after weaning reduced the incidence of PWD commensurate with a reduction in protein fermentation indices.